2014
DOI: 10.1590/1413-81232014193.01182013
|View full text |Cite
|
Sign up to set email alerts
|

Mortes infantis evitáveis por intervenções do Sistema Único de Saúde: comparação de duas coortes de nascimentos

Abstract: Comparou-se a mortalidade infantil evitável nas coortes de nascimentos de 2000/2001 e de 2007/2008, em Londrina-PR. Dados sobre nascidos vivos e óbitos infantis foram vinculados em base de dados única e as causas básicas de morte foram agrupadas conforme a Lista Brasileira de Causas de Mortes Evitáveis por Intervenções do Sistema Único de Saúde. Calculou-se a variação percentual das taxas de mortes entre os biênios e usou-se a técnica de análise de correspondência. As proporções de óbitos evitáveis foram de 71… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 22 publications
5
15
0
11
Order By: Relevance
“…It is noteworthy that external cause was the second most frequent cause in both neonatal and post-neonatal components, specifically due to gastric aspiration. This result was confirmed in another study that showed that death from gastric aspiration was outstanding among deaths from external causes (28) . Most of these events occur with no medical assistance, at home or on the way to the health service.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…It is noteworthy that external cause was the second most frequent cause in both neonatal and post-neonatal components, specifically due to gastric aspiration. This result was confirmed in another study that showed that death from gastric aspiration was outstanding among deaths from external causes (28) . Most of these events occur with no medical assistance, at home or on the way to the health service.…”
Section: Discussionsupporting
confidence: 57%
“…Most of these events occur with no medical assistance, at home or on the way to the health service. Therefore, care should be focused on prevention and coordination with different care levels for each stage of development of the child, and quick access to proper instructions in the event of accident (28) . That is why childcare starts in the prenatal period with group activities for pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…Although this study has not analyzed the causes of deaths among low birth weight newborns, we note that these deaths mostly occur due to preventable causes, especially through adequate care to women during pregnancy (18) , which reinforces the need to invest in the training of pre-natal care services available in the Brazilian Unified Health System.…”
Section: Resultsmentioning
confidence: 88%
“…Although congenital anomalies are significantly considered on the statistics of morbidity and infant mortality, representing the second leading cause of neonatal death in Brazil (21) , they have been little explored in mortality studies, most likely because they are not classified as preventable deaths, mostly unknown etiology and therefore, difficult to reduce (18) . In the present study, the presence of congenital anomaly was associated with death, with a greater chance of neonatal death compared to those born without malfunction.…”
Section: Neonatal Mortality In Infants With Low Birth Weighmentioning
confidence: 99%
“…Estudos demonstram que o acesso aos serviços obstétricos não é igualitário 6,7 , há iniquidade na distribuição de unidades e leitos 8 , inadequações de estrutura das maternidades 9,10 , persistência no desenvolvimento das práticas obstétricas não recomendáveis, tais como uso de ocitocina, episiotomia, manobra de Kristeller, entre outras 4,5,11,12 , além do aumento constante das taxas de cesarianas, da prematuridade e do baixo peso ao nascer caracterizando a fragilidade dos cuidados prestados 13,14,15 .…”
Section: Introductionunclassified